MITIGATE TYPE II AGENCY CONFLICT THROUGH GOOD CORPORATE GOVERNANCE AND DISCLOSURE QUALITY - Citrawati Jatiningrum; Fauzi Fauzi; Bernaditha H.S Utami; Aza Azlina Md Kassim (AKUNTABILITAS, 2023)
Empirical evidence on type II conflicts between controlling shareholders versus minority shareholders has not been extensively explored.  This study gives new evidence on the agency conflict in a scenario of highly concentrated ownership. This study aims to examine the effect of Good Corporate Governance mechanism with quality of disclosure on concentrated ownership context The sample were drawn from companies listed on the Indonesia Stock Exchange (IDX). The data were analyzed with panel data regression. The results shows that CG mechanisms negatively effects with DQ. However, looking at each individual variable, the study reveals that the audit committee and independence of audit committee are not significant. A possible reason is that companies' audit committee members have lack of accounting expertise and independence. These findings shed light on the concept of good CG enhances incentives for good DQ under highly concentrated ownership. It the effectiveness of CG mechanisms is likely to supplement regulation to protect investor rights and may prove to be useful for standard-setters as an important way to reduce agency conflicts.